Pedagogical models of blended learning: On the experience of Russian and foreign practice of design and implementation - T. Yu. Pletyago; A. S. Ostapenko; S. N. Antonova (Образование и наука)
Introduction. One of the strategic components of modern education modernisation is its technological diversification by means of traditional and emedia blend in the educational process aimed at acquiring knowledge, skills and competences. This blend is considered a trigger for innovative development of higher education worldwide due to its adequate adaptive personalised professional training for students. Thereby, to interpret and evaluate the pedagogical potential for blended learning models implementation in higher education environment is regarded as foremost.The aim of the article is to theoretically and practically provide rationale for the efficiency of structural and functional content of the existing blended learning models that designate specific patterns for education management in Russian and foreign universities.Methodology and research methods. System approach underlies this research. Retrospective and comparative analysis methods, synthesis and classification have been employed to conduct the research. A survey is a supplementary method used to collect empirical data.Results and scientific novelty. The existing definitions of blended learning are reviewed. Pedagogical models of blended learning are compared according to their dominant functional feature, design principles and basic components. The models are classified into institutional, technological, didactic and synergistic on the basis of synthesis and systematisation of the theoretical and practical experience of an integrative didactic teaching system design in the university electronic educational environment. Each type of these models is described; their features, peculiarities and advantages are shown. It is concluded that there is no unified approach in understanding the essence of blended learning. Thus, the authors’ interpretation of the blended learning concept is developed in the research.Practical significance. The results of the research may be applied in design, implementation and assessment performance of blended learning models or their components in practice of particular universities.